The use of paper dictionary on L2 vocabulary learning and retention - Zuraina Ali (Universitas Ahmad Dahlan, 2021)
Vocabulary learning and retention are the two components that are essential in assessing students' abilities to understand the meaning of words. The study examines students’ attitudes of learning vocabulary and their learning feedback of using a paper dictionary. It also investigates the factors that students favour and dislike when using the resources for vocabulary retention. The method uses to collect the data in the current study is Explanatory Sequential Research Design. Both questionnaires and semi-structured interviews are employed as the instruments in the current study. The study found that students had positive learning attitudes using paper dictionary in learning vocabulary. There was also various learning feedback that was obtained concerning the use of the resource for the learning of vocabulary. In terms of vocabulary retention, students provided different viewpoints in the use paper dictionary to assist them in memorising the definition of a target word. Finally, the study found a few factors that restricted them to use the resources to retain the vocabulary learnt. The study implies that the use of a paper dictionary is still significant as it helped students to enhance their understanding of a particular vocabulary.